“The Disclosure of Divine Liturgy” by Pseudo-Gregory of Nazianz: medieval Slavonic translations and existing scholarly studies of the text - Michael Zheltov (Вестник Православного Свято-Тихоновского гуманитарного университета: Сериа III. Филология)
This article is devoted to an important yet understudied monument of the medieval Orthodox Christian culture, “The Disclosure of the Divine Liturgy”, attributed to St. Gregory of Nazianz in manuscripts. This text has been known for a long time in Old Russian manuscripts, but its Greek original remained unpublished until 2015, when the author of this article made public his edition of the text in Bollettino della Badia Greca di Grottaferrata. The present article contains a survey of the existing studies of Slavonic translations of “The Disclosure of the Divine Liturgy” and of the relevant publications by art historians, in chronological order. The Greek text (reprinted here for the sake of convenience) is accompanied by a new translation into modern Russian and is compared to its Slavonic versions. As has been noted by Tatyana Afanasyeva, there is a number of Old Russian manuscripts among the Slavonic manuscripts of the text, containing two or three diff erent versions of the text, and the unique (at least at the moment) South Slavonic codex containing a separate version. Afanasyeva further states that all of the Old Russian redactions can be traced to a single Old Russian translation, while the South Slavonic translation might have been made in the “Old Slavonic period”, though later reworked. In order to prove this statement, she cites a list of “archaic” linguistic features in the South Slavonic version of the piece. The present article confi rms that all of the Old Russian redactions of the text do belong to the same translation. This is firmly proved by a number of mistranslated words or word combination that reoccur in all of the Old Russian versions of the text, which means that the successive Russian editors had no access to the original Greek text. Meanwhile, Afanasyeva’s claim that the South Slavonic version of the text goes back to an “Old Slavonic” translation should be decisively rejected on the basis of the following two arguments. First, the composition of the Greek text itself is dated to 12th century, as the author of this article has shown in detail earlier. Second, none of the aforementioned “archaic” linguistic features stand up to criticism. Therefore, both of the independent Slavonic translations of “The Disclosure of the Divine Liturgy” should belong to approximately the same period, namely the 12th century or the fi rst third of the 13th century.